2021
DOI: 10.3390/ijms22094574
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of GPR17-Expressing Cells Correlates with White Matter Inflammation Status in Brain Tissues of Multiple Sclerosis Patients

Abstract: In multiple sclerosis (MS), oligodendrocyte precursor cells (OPCs) are recruited to the site of injury to remyelinate damaged axons; however, in patients this process is often ineffective due to defects in OPC maturation. The membrane receptor GPR17 timely regulates the early stages of OPC differentiation; however, after reaching its highest levels in immature oligodendrocytes, it has to be downregulated to allow terminal maturation. Since, in several animal models of disease GPR17 is upregulated, the aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…↓ proliferation [188] P2Y 12 R ? Downregulated in the cerebral cortex of post-mortem MS brains [113,189] Uracil-nucleotides GPR17R ↑ migration [87] Overexpressed in active lesion of post-mortem MS brains [190] ↑ differentiation [87,191] [117,118] ?…”
Section: Neurotransmitters In Oligodendroglial Cells and Myelinationmentioning
confidence: 99%
See 1 more Smart Citation
“…↓ proliferation [188] P2Y 12 R ? Downregulated in the cerebral cortex of post-mortem MS brains [113,189] Uracil-nucleotides GPR17R ↑ migration [87] Overexpressed in active lesion of post-mortem MS brains [190] ↑ differentiation [87,191] [117,118] ?…”
Section: Neurotransmitters In Oligodendroglial Cells and Myelinationmentioning
confidence: 99%
“…On the other hand, at later stages, i.e., CNPase + /O1 + cells, its overexpression impairs final OL differentiation and myelination in vitro [ 212 ]. Of note, recent data demonstrated that GPR17 is overexpressed in active lesions and in NAWM of post-mortem MS brains [ 190 ].…”
Section: Neurotransmitters In Oligodendroglial Cells and Myelinationmentioning
confidence: 99%
“…Interestingly, the transcriptional network of the latter relates cell-cell adhesion and viability, whereas they did not present high expression of myelin genes (as Oligo3 and Oligo4 cluster), suggesting that not all mature OLs maintain a strongly active transcriptional machinery for myelination. The intermediate Oligo6 cells, which are extremely enriched in Opalin, and Oligo1, were found significantly reduced in MS, both in normal-appearing white matter and lesions, adding evidence to the concept that normalappearing white matter is indeed not "normal" (de Groot et al, 2013;Angelini et al, 2021). On the contrary, Oligo2, Oligo3, Oligo5 and imOLs, which are closely associated with microglia, have been found enriched in MS, suggesting that MS pathophysiology may not be strictly associated with a global failure of differentiation, but rather with a skew in specific subpopulations.…”
Section: Unraveling Oligodendroglial Heterogeneity With Single-cell Omicsmentioning
confidence: 79%
“…OPC1 expressed high levels of Clusterin, a gene found upregulated in both Alzheimer’s disease and MS, suggesting that these cells may play an active role in these diseases. OPC cluster 2 showed enrichment in multiple proteins involved in ECM organization and cytokine mediated signaling, whereas OPC3 showed significant upregulation of the G protein-coupled receptor (GPR17), a promising target for remyelination therapies ( Bonfanti et al, 2020 ; Parravicini et al, 2020 ; Angelini et al, 2021 ) and up-regulation of several genes related to neuronal differentiation and synapse organization.…”
Section: Unraveling Oligodendroglial Heterogeneity With Single-cell Omicsmentioning
confidence: 99%
“…Overexpression of GPR17 has been described in several models of disease such as brain ischemia [ 14 ], cuprizone- and lysolecithin-induced demyelination [ 15 , 16 ], Alzheimer’s-like conditions [ 17 ], amyotrophic lateral sclerosis [ 18 ] and experimental autoimmune encephalomyelitis (EAE) [ 15 , 19 ]. Marked GPR17 upregulation and/or accumulation of GPR17-expressing cells at the border of demyelinated lesions has been also observed in patients affected by MS [ 19 , 20 ], traumatic brain injury [ 21 ] and congenital leukoencephalopathy [ 22 ]. In the presence of strong pro-inflammatory conditions, GPR17-expressing cells accumulate at lesion sites, remaining stuck at intermediate stages and not able to contribute to remyelination, suggesting that dysregulation of receptor downregulation contributes to remyelination failure and disease progression.…”
Section: Introductionmentioning
confidence: 99%